“Dia merasa dan berpikir”: Emotion and mental state talk ibu pada konteks membaca buku - Putri, Tasya Nafasya; Kuntoro, Ike Anggraika; Nurdin, Dien Nurdini (Jurnal Psikologi Ulayat, 2024)
Mother's emotion and mental state talk (EMST) in storybook reading context has been reported to be positively correlated with children's social understanding. Previous findings postulate that cultural context and book formats could affect the emergence of EMST. On the contrary, research about the EMST in the Indonesian cultural context and in various book formats is limited. Hence, further research needs to be conducted to explore the characteristics of EMST in Indonesian families. The current study aims to analyze which type of EMST is preferred by mothers in Indonesia, the frequency of EMST usage across various levels of reading difficulty, and the functions of EMST among Indonesian mothers. Secondary data were analyzed qualitatively from parents' video recordings of reading book activities. The main findings of this research suggest that, while most participants reported utilizing desire talk as a means of EMST, they were more likely to emphasize character descriptions, storylines, or general knowledge compared to EMST in shared book reading sessions. The lack of spontaneous EMST in Indonesian mothers may reflect the cultural influence on the expression of emotions and mental states in everyday life.